Gold Nanoparticles from Vegetable Extracts Using Different Plants from the Market: A Study on Stability, Shape and Toxicity. Issue 30 (25th October 2017) - Clemente, Ilaria; Ristori, Sandra; Pierucci, Federica; Muniz‐Miranda, Maurizio; Salvatici, Maria Cristina; Giordano, Cristiana; Meacci, Elisabetta; Feis, Alessandro; Gonnelli, Cristina
Abstract: The use of nanoparticles for many advanced applications (drug‐delivery, biosensors, catalysts etc.) involves their large scale production. This engenders the need of synthetic methods and reactants which are sustainable as well as safe. Natural products allow to prepare nanoparticles via eco‐friendly processes, which is especially true for reducing/capping agents obtained from agricultural by‐products. Here, we prepared gold nanoparticles (AuNPs) in high yields by using extracts from the leaves of marketable plants and by following different synthetic routes (i. e. one‐ or two‐steps). The size and morphology of the obtained AuNPs were determined by Transmission Electron Microscopy (TEM), while surface coverage with different chemical species was investigated by surface‐enhanced Raman scattering (SERS). In vitro experiments on bone‐marrow mesenchymal stromal cells (MSCs) were used to study the effect on cell viability, as a first step toward toxicity assessment. This work allowed to select the nanoparticles with highest SERS activity at infrared excitation wavelength, in view of their possible use as shelf products. Abstract : The synthesis of gold nanoparticles from various plant extracts gave systems with different morphology, SERS activity and in vitro behavior toward human cells. We showed that both the synthetic route and the plant type discriminate the gold nanoparticle outcome, thus evidencing the challenge to balance tunability of properties, safety and large scale production.